Ações sociorrecreativas para idosos: um protocolo de atividade para o jogo do câmbio - Oliveira, Ellen Correia Fonseca de (2021)
Introduction: Human aged is an irreversible process. It is accompanied by several changes in life of the subject, when takes on fundamental importance the incentive to the practice of physical activities as strategie to the promotion of health and in consequence preservation of the autonomy and physical and intelectual independence. Objectives: to investigate scientific evidences about social-amusement actions, aiming capacity or ability of an stability of health in aged; to analyse, modalities of sport directed to aged in the geographic area of João Pessoa, capital of state of Paraiba, and to elaborate a Protocol of pedagogical strategie from basic fundamentals in game of Exchange in the perspective to stablish an coexistence with the rules “into effect to each modality”. Methods: It is a methodological study developed in three stages: Integrative review of literature; research of field exploratory and descritive one, with an approach a quantitative of datas based from a sample of nineteen sportive federations, and the validation of a protocol of activities to the game of exchange. It was used a ‘road map” of semi structured interview to the colect of dice of research. The collect dice were inserted in an eletronie Spreasheet Excel and transported to Statistic analysis in the SPSS programme for windows, version 26.0 and they were analysed through the descritive statistic and presente pictures and graphics. Results and discussion: In the integrative review were selected seventeen articles which identified social-recreative actions directed to aged. In the field research it was observed that all the representatives of federative unities the Presidents were in majority from masculine gender (100%) “89,4%”. The great number of sport federations (52,6%) was founded after the decade of ninety, with 42,1%. It was composed by eight members with 84,2% of them with mandate of four years, through theelection fullfilled through vote among the associated in 84,2% of them. The majority of sport federations (42,1%) presented a quantitative between one to ten aged athletes, the search of this public to the sportive modalities was 68% and generally composed by ex-athletes in the order of 63,1%. In relation to the existence of specific cathegory to the aged corresponded to (89,4%) presented only in three sportive modalities were grouped by terrestrial sports; aquatic ones; fights and air sports. Only four sports indicated specific rules to the aged, for example the reduction of time of the game or the fight and the greater number of substitutions during the match. Ultimately it was elaborated and validated a protocol that organizes in its content the “step by step” to standardize the possible rules to the game of exchange. Final Considerations: In according to the findings of the research it was the fragility in the relation to the insertion of the aged in sport. The developed protocol provides information about the importance of standardizing the rules of games in exchange as an Educative Resource capable of subsidizing the professionals to organizing and preparing the old aged according to their physical performance being possible make it a sport.